Raising complex public health challenges on local government agendas: a Norwegian case study - Kristine Løkås Vigsnes; Charlotte Kiland; Harry Rutter; Eirik Abildsnes (Health Research Policy and Systems)
Abstract Background Public health challenges, ranging from noncommunicable disease prevention to pandemic preparedness, involve both policymaking and the handling of complexity at local, national or global level. The complexity of public health challenges arises from uncertain knowledge, hidden mechanisms, differing conceptual models and multiple stakeholders, making it difficult to identify and agree on problem definitions and potential solutions. This case study aims to provide insights into how complex public health challenges are addressed within local government agendas. We use theories of policy entrepreneurs and agenda setting to explore the processes behind the agenda setting of a public health programme for work inclusion. Methods We conducted an in-depth case study in a local government context. Data from interviews with key informants and political documents were triangulated and analysed using deductive thematic content analysis, framed within Kingdon’s agenda-setting theory and theories of policy entrepreneurs. Results We identified problem framing, the involvement of multiple actors, and turbulent surroundings as influential factors for agenda setting of complex public health challenges in local government. We further identified the significance of the level of influence of policy entrepreneurs’ positions, their coalitions and maintaining agenda control as core mechanisms for enabling agenda setting. We found that strategic manoeuvres of policy entrepreneurs were crucial to handle and manoeuvre complexity within the multiple streams described by Kingdon. Conclusions This article contributes knowledge of how complex public health problems receive attention and how these issues are shaped and defined, placed on governmental agendas, and paired with solutions. The article contributes important insights for understanding policy responses to complex public health problems and how policy entrepreneurs strategically manoeuvre within the streams of policy development to create windows of opportunity and maintain agenda control. This is important knowledge to support agenda setting for public health challenges and to realize policies to improve public health.